PEMBELAJARAN MATRI PERAN INDONESIA DI ERA GLOBAL PADA SISWA SD KELAS VI DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING(PBL)MELALUI SETTING KOOPERATIF TIPE TEAMS GAMES TOURNAMENT(TGT) - Tanty Laksanawati (COLLASE (Creative of Learning Students Elementary Education), 2021)
The purpose of this study is to describe (1) the scenario and implementation of learning the role of Indonesia in the Global Era through the Problem Based Learning (PBL) learning model through the Team Games Tournament (TGT) type cooperative setting in grade VI students, (2) teacher and student responses class VI on learning material on the role of Indonesia in the global era, (3) the difficulties experienced by grade VI students in completing the subject matter of Indonesia's role in the global era. This research method is descriptive qualitative research. The participants of this research were teachers and students. Data collection techniques used in the study were observation, questionnaires and interviews. Data analysis in qualitative research was carried out before entering the field, during the field and after finishing the field. The results of scenario research and the implementation of learning carried out by the teacher can be seen with the improvement in learning, students become more active in learning. The teacher and student responses both can be seen from the results of the questionnaire given during the lesson. The difficulty experienced by students with this material is only in the question indicators explaining the meaning of globalization, but most students do not experience difficulties in the material. Conclusions based on the results of research on scenarios and implementation of learning material on Indonesia's Role in the Global Era with the Problem Based Learning (PBL) learning model through the cooperative setting type Teams Games Tournament (TGT) in grade VI SDN Gandasari the results are good and the steps taken by the teacher are already corresponding. The teacher's response in learning the material on Indonesia's Role in the Global Era has been good, as well as student responses to learning have been good. Difficulties experienced by grade VI students in completing the material on Indonesia's role in the global era. Students have difficulty in the question indicator explaining the meaning of globalization. The average student answered incorrectly on the test questions given by the teacher. However, most students do not experience difficulties in the material on Indonesia's role in the global era. As for the other factors that became students' difficulties based on the results of the interviews, namely students were difficult to memorize and understand so much subject matter. Many students have difficulty answering questions in essay form.